Eletrodo Modificado com [CoO(OH)] Coloidal Aplicado na Detecção de Ácido Oxálico - Stadnik, Andréia; Caldas, Elisângela M.; Galli, Andressa; Anaissi, Fauze J. (Orbital: The Electronic Journal of Chemistry, 2015)
In this work, we used a chemically modified electrode with cobalt oxyhydroxide in colloidal form as an electrochemical sensor for oxalic acid. Initial experiments were performed in different electrolytes (LiOH, NaOH e KOH), that better defined electrochemical response in medium NaOH solution [0.5 mol.L-1]. From measurements of cyclic voltammetry and square wave voltammetry for quantification of oxalic acid responses electroanalytical was obtained for concentrations in order 10-5-10-6 mol L-1. The detection limits (2.52x10-5 mol.L-1) and quantification (7.55x10-6 mol.L-1) were significantly better for measurements performed by square wave voltammetry. The CME-Co has potential application as a sensor for the measurement of oxalic acid and redox species. DOI: http://dx.doi.org/10.17807/orbital.v7i2.572